Basic aerodynamics incompressible flow - Flandro, G. A. 1934- (Cambridge University Press, 2012)
"In the rapidly advancing field of flight aerodynamics, it is important for students to completely master the fundamentals. This text, written by renowned experts, clearly presents the basic concepts of underlying aerodynamic prediction methodology. These concepts are closely linked to physical principles so that they may be more readily retained and their limits of applicability are fully appreciated. The ultimate goal is to provide the student with the necessary tools to confidently approach and solve of practical flight vehicle design problems of current and future interest. The text is designed for use in course in aerodynamics at the advanced undergraduate or graduate level. A comprehensive set of exercise problems is included at the end of each chapter"-- Provided by publisher.
Keywords: Air flow -- Textbooks.; Aerodynamics -- Textbooks.; elektronické knihy; electronic books